Men's intrusion, women's embodiment: a critical analysis of street harassment - Vera-Gray, Fiona (Routledge, 2017)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité; angleterre; approches et analyses; corps; discipline; europe; harcèlement de rue; patriarcat; phénoménologie; périodes historiques; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Les rabat-joie féministes (et autres sujets obstinés) - Ahmed, Sara (Cahiers du Genre, 2012)
Interrogeant la figure de la « féministe rabat-joie », cet article propose d’en explorer la négativité, aussi bien que la capacité d’agir dont elle est la promesse. Il s’agit ainsi, en repositionnant la pensée féministe comme critique de l’injonction au bonheur, de comprendre le sujet féministe en tant que sujet obstiné. L’obstination féministe est alors appréhendée comme le socle incertain d’une politique collective traduisant les émotions individuelles, la douleur ou la colère ressentie face aux injustices. Au-delà, la figure du sujet obstiné permet de saisir la façon dont, au sein des espaces féministes, les femmes noires ont pu être réduites à leur colère et désignées comme cause des divisions engendrées par le racisme. La position de sujet obstiné constituerait ainsi autant un lieu de tensions que de revendications politiques. https://www.saranahmed.com/
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; care; cours; discipline; europe; fem1000; féminismes noirs; incontournable; intersectionnalité; luttes; militance; occident; orient; philosophie; phénoménologie; politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Transformative conversations about sexualities pedagogy and the experience of sexual knowing - Trimble, Lisa (Sex Education : Sexuality, Society and Learning, 2009)
One of the hallmarks of sex education traditionally has been its Cartesian endorsement of mind/body dualism; we have preferred to equate ‘self’ as synonymous with ‘mind’, and have invested heavily in believing in the valence of rationality‐based sexualities education. We generally do not consider the way ‘self’ negotiates, interprets and relates to sexual knowledge in all of our complexity, including our messy, embodied and emotional lives. In this paper I address what I think are several much‐needed conversations for a holistic pedagogy of sexualities to incorporate, including the falseness of the mind/body split, reconsidering what counts as sexual knowledge, the role of the performative in communicating our sexual knowing, and the importance of considering affect in learning about sexualities. The second part of the paper examines pedagogical considerations currently absent in dialogues of sexualities education, such as incorporating transformational learning strategies in teaching sexualities, and what it means to educate toward being a sexual citizen. Finally, I will outline how discussions of epistephenomenology (our relationship to and how we experience knowledge) can contribute to moving toward a vision of a critical, cultural sexualities education.
Number: 1
Keywords: approches et analyses; corps; discipline; discours dominant; phénoménologie; ressource en ligne; savoir expérientiel; science de l'éducation; sciences humaines; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; émotions; épistémologie

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Rowman & Littlefield, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Section: x, 193 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Femininity and domination: studies in the phenomenology of oppression - Bartky, Sandra Lee (Routledge, 1990)
Bartky s'appuie sur l'expérience de la vie quotidienne pour démasquer les nombreux déguisements par lesquels les intimations d'infériorité sont infligées aux femmes. Elle critique à la fois le parti pris masculin de la théorie actuelle et la domination débilitante détenue par les notions de «féminité appropriée» sur les femmes et leurs corps dans la culture patriarcale.
Keywords: 1900-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; lit3220; patriarcat; phénoménologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; états-unis